And the mountains echoed : Dan gunung-gunung pun bergema / Khaled Hosseini; Penerjemah, Berliani Mantili Nugrahani; Editor, Esti A. Budihapsari - HOSSEINI, Khaled; BERLIANI Mantili Nugrahani; ESTI A. Budihabsari (Qanita, 2014)
516 hlm. ; 20,5 cm.